United States Africa Partnership Station Programme and Maritime Security Governance in the Gulf of Guinea: Niger Delta in Perspective - Obi, Kelechukwu Charles; Nwaogidu, John Chidubem; Asogwa, Kenneth Chinedu (University of Nigeria Journal of Political Economy, 2025)
The Africa Partnership Station Programme was implemented by the US in collaboration with the coastal states as a structural response to the growing insecurity in the GoG. In spite of the collective efforts aimed at improving the maritime situation and to foster uninterrupted energy production and access, reports show that there has been a surge in criminal activities in the GoG. This study interrogates the US Africa Partnership Station Programme and maritime security governance in the GoG, using Niger Delta as a reference point. Documentary method of data collection and Qualitative descriptive method of data analysis were adopted. The study applied the key propositions of the Marxist Structuralist theory of the state to apprehend the moribund activities of the APS and increasing maritime criminalities in the coast of the Niger Delta as partly a direct consequence of the impaired institutional capacity of the maritime security and law enforcement agencies occasioned by the logic of sustaining the viability of the rolling global capitalist mode of production.